Alkali slag lightweight high-strength concrete as well as preparation method and application thereof
By using gelling materials, shale ceratops and composite alkali exciters in alkali slag lightweight high-strength concrete, combined with hollow glass microbeads, the problems of density and strength of lightweight high-strength concrete in the prior art are solved, and lighter And high-performance concrete is suitable for high-rise buildings and large-span buildings.
Patent Information
- Application Number
- CN202411233091.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-17
AI Technical Summary
The existing lightweight high-strength concrete is difficult to maintain strength while reducing density, and the porous structure of the ceramite leads to a decrease in strength, and there is less lightweight high-strength concrete prepared under the alkali slag gelling material system.
The alkali slag lightweight high-strength concrete is used to combine cementitious materials, shale ceratops and composite alkali excitants to replace cement by slag powder and silica fume in the cementitious materials, and further reduce the density with hollow glass microbeads. Shale ceratops are selected. As aggregate to improve mechanical properties.
While maintaining mechanical properties, it significantly reduces concrete density and reduces carbon emissions. It is suitable for high-rise buildings and large-span buildings with strict requirements on concrete weight, achieving resource conservation and sustainable development.
Smart Images

Figure BDA0005026869460000041 
Figure BDA0005026869460000042 
Figure BDA0005026869460000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete materials, and specifically relates to an alkali-slag lightweight high-strength concrete and a preparation method and application thereof. Background Art
[0002] At present, with the rise of new building structures and components such as prefabricated buildings and large-span structures, lightweight prefabricated structures have become an inevitable requirement for industrialized building installation and rapid construction, so as to achieve self-compacting concrete, thereby effectively avoiding concrete segregation caused by irregular vibration at the construction site. With the rapid development of building industrialization and the world's requirements for building energy conservation, lightweight and self-compacting have become an inevitable trend in the development of cement-based materials.
[0003] Lightweight high-strength concrete (LWHSC) refers to a concrete with a dry apparent density of no more than 1950 kg / m3, which is made of high-strength lightweight coarse aggregate (such as high-strength ceramsite), ordinary sand, cement and water. 3 , lightweight concrete for structures with strength grade above LC30. Alkali slag cementitious material is a new type of cementitious material composed of two parts, mainly granulated blast furnace slag and alkali activator (prepared by alkaline chemical solution). It is a hydraulic cementitious material made by the catalytic principle of alkali activator (caustic alkali, alkali-containing silicate, aluminate), and alkali slag lightweight high-strength concrete combines the above two. Most lightweight high-strength concretes are prepared based on ordinary Portland cement system, while there are few lightweight high-strength concretes prepared under alkali slag cementitious material system.
[0004] In terms of lightweight aggregate, lightweight expanded clay is usually chosen to fill the volume inside concrete to reduce the weight of concrete. However, expanded clay has a porous structure and has the characteristics of large porosity resulting in reduced strength. In addition, the larger the particle size of expanded clay, the more pores there are and the more significant the decrease in strength. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes an alkali-slag lightweight high-strength concrete, which is obtained by combining lightweight high-strength concrete and alkali-slag cementitious material, and further reduces the density of concrete while maintaining the overall mechanical properties of concrete, and is more suitable for projects with strict requirements on the weight of concrete.
[0006] The present invention also provides a method for preparing the alkali-slag lightweight high-strength concrete.
[0007] The present invention also proposes the application of the alkali-slag lightweight high-strength concrete.
[0008] According to the first aspect of the present invention, it is proposed that the alkali-slag lightweight high-strength concrete comprises the following components: cementitious material, shale pottery sand and composite alkali activator;
[0009] The cementitious material includes slag powder and silica fume;
[0010] The composite alkali activator comprises sodium silicate and potassium carbonate.
[0011] In some embodiments of the present invention, the alkali-slag lightweight high-strength concrete includes the following components in parts by weight: 700-900 parts of cementitious material, 400-700 parts of shale pottery sand, and 100-200 parts of composite alkali activator.
[0012] In some preferred embodiments of the present invention, the alkali-slag lightweight high-strength concrete comprises the following components in parts by weight: 800-850 parts of cementitious material, 450-700 parts of shale pottery sand and 120-160 parts of composite alkali activator.
[0013] In some embodiments of the present invention, the alkali-slag lightweight high-strength concrete further includes 150 to 250 parts by mass of water.
[0014] In some preferred embodiments of the present invention, the alkali-slag lightweight high-strength concrete further comprises 180 to 200 parts by mass of water.
[0015] In some preferred embodiments of the present invention, the mass ratio of sodium silicate to potassium carbonate in the composite alkali activator is (1-2):1.
[0016] In some more preferred embodiments of the present invention, the mass ratio of sodium silicate to potassium carbonate in the composite alkali activator is (1.3-1.5):1.
[0017] In some preferred embodiments of the present invention, the mass ratio of slag powder to silica fume in the cementitious material is (6-9):2.
[0018] In some more preferred embodiments of the present invention, the mass ratio of slag powder to silica fume in the cementitious material is (3-4):1.
[0019] In some embodiments of the present invention, the gelling material further comprises hollow glass microspheres.
[0020] In some preferred embodiments of the present invention, the mass ratio of the hollow glass microspheres to the silica fume is 10:(2-7).
[0021] In some more preferred embodiments of the present invention, the mass ratio of the hollow glass microspheres to the silica fume is 10:(3-6).
[0022] In some embodiments of the present invention, the particle size of the shale ceramic sand is 0.15 to 4.75 mm.
[0023] In some embodiments of the present invention, the apparent density of the shale sand is 1400-1700 kg / m 3 .
[0024] In some preferred embodiments of the present invention, the apparent density of the shale ceramic sand is 1500-1600 kg / m 3 .
[0025] In some preferred embodiments of the present invention, the true density of the hollow glass microspheres is 0.4 to 0.8 g / cm 3 .
[0026] In some more preferred embodiments of the present invention, the true density of the hollow glass microspheres is 0.5 to 0.7 g / cm 3 .
[0027] In some preferred embodiments of the present invention, the bulk density of the hollow glass microspheres is 0.25 to 0.5 g / cm 3 .
[0028] In some more preferred embodiments of the present invention, the bulk density of the hollow glass microspheres is 0.35 to 0.45 g / cm 3 .
[0029] In some preferred embodiments of the present invention, the compressive strength of the hollow glass microspheres is 70 to 90 MPa.
[0030] In some more preferred embodiments of the present invention, the compressive strength of the hollow glass microspheres is 80-85 MPa.
[0031] In some embodiments of the present invention, the apparent density of the alkali-slag lightweight high-strength concrete is 1400-1700 kg / m 3 .
[0032] In some preferred embodiments of the present invention, the apparent density of the alkali-slag lightweight high-strength concrete is 1440-1670 kg / m 3 .
[0033] In some embodiments of the present invention, the 28d compressive strength of the alkali-slag lightweight high-strength concrete is 65-90 MPa.
[0034] In some preferred embodiments of the present invention, the 28d compressive strength of the alkali-slag lightweight high-strength concrete is 68-83 MPa.
[0035] According to a second aspect of the present invention, a method for preparing the alkali-slag lightweight high-strength concrete as described in the first aspect of the present invention is provided, the preparation method comprising the following steps:
[0036] The shale pottery sand is stirred, and then the cementitious material is added and mixed to obtain a cementitious mixture;
[0037] The sodium silicate and potassium carbonate are mixed with water to obtain a composite alkali activator, and the composite alkali activator is mixed with a cementitious mixture to obtain an alkali-slag lightweight high-strength concrete.
[0038] According to the third aspect of the present invention, the use of the alkali-slag lightweight high-strength concrete according to the first aspect of the present invention in the preparation of lightweight concrete panels is proposed.
[0039] In some embodiments of the present invention, the lightweight concrete panel can be used for the construction of high-rise buildings and / or long-span buildings.
[0040] The present invention has at least the following beneficial effects:
[0041] 1) The alkali-slag lightweight high-strength concrete provided by the present invention is obtained by combining an alkali-slag cementitious material and a lightweight high-strength concrete. The alkali-slag cementitious material uses industrial solid wastes such as silica fume and granulated blast furnace slag powder to completely replace cement, thereby reducing cement usage and reducing carbon emissions; and the lightweight aggregate uses shale pottery sand. Compared with ordinary aggregates, the amount of shale pottery sand in concrete is lower, and a high mechanical strength is achieved with a low amount of aggregate, which can save resources and conform to the concept of sustainable development;
[0042] 2) The alkali-slag lightweight high-strength concrete provided by the present invention adopts high-performance hollow glass beads to replace part of the slag powder to further reduce the density of the concrete, making the concrete lighter while maintaining the mechanical strength. It is suitable for high-rise buildings and large-span building construction projects that have strict requirements on the weight of concrete. DETAILED DESCRIPTION
[0043] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0044] Materials and Methods
[0045] In the following examples and comparative examples provided by the present invention, the physical property parameters of the raw material components used are as follows:
[0046] The mineral powder used is S95 slag powder, and its specific chemical composition and various physical performance parameters are shown in Tables 1-2.
[0047] Table 1 Main chemical components of slag powder
[0048]
[0049] Table 2 Physical properties of slag powder
[0050]
[0051] The shale ceramic sand used is made from crushed shale ceramsite, with a particle size of 0.15-4.75 mm and an apparent density of 1545 kg / m 3 The fineness modulus is 2.9. The particle grading screening results of the shale ceramic sand are shown in Table 3.
[0052] Table 3 Particle grading screening results of shale ceramic sand
[0053]
[0054]
[0055] The true density of the hollow glass microspheres used is 0.60 g / cm 3 , the bulk density is 0.39g / cm 3 , particle size distribution is 70μm and compressive strength is 82MPa.
[0056] Example 1
[0057] This embodiment provides an alkali-slag lightweight high-strength concrete, and the preparation method of the alkali-slag lightweight high-strength concrete comprises the following steps:
[0058] 1. Calculate the mix ratio between the components:
[0059] The mix ratio of each component is calculated by absolute volume method in accordance with the industry standard JGJ / T 12-2019 "Technical Standard for Application of Lightweight Aggregate Concrete"; the water consumption is 190 kg, the water-binder ratio is 0.23, and the mix ratio of cementitious materials is calculated according to the following formula:
[0060] Among them, m b is the mass of cementitious material, w is the water consumption, and k is the water-cement ratio.
[0061] The cementitious material includes slag powder and silica fume, which account for 80% and 20% of the mass of the cementitious material respectively, that is, slag powder is 660.87kg and silica fume is 165.22kg; the composite alkali activator is prepared by mixing water, sodium silicate and potassium carbonate. The amount of sodium silicate and potassium carbonate is screened by preliminary experiments, and the amount is 10% and 7% of the mass of the cementitious material respectively, that is, sodium silicate is 83.44kg and potassium carbonate is 58.57kg; after measurement, the mass of the mixed composite alkali activator is 331.74kg and the density is 1340kg / m 3 .
[0062] The amount of shale sand is calculated according to the following formula:
[0063]
[0064] m s =V s ρ s =0.44×1545=679.8kg;
[0065] Among them, m1 is the mass of slag powder, m2 is the mass of silica fume, m3 is the mass of composite alkali activator, and m s is the amount of shale sand, ρ1 is the density of slag powder, ρ2 is the density of silica fume, ρ3 is the density of composite alkali activator, ρ s is the density of shale sand, V s is the absolute volume of shale sand, S p is the absolute volume sand ratio.
[0066] 2. Mixing, molding and curing:
[0067] 1) According to the above calculation results, weigh 660.87kg slag powder, 165.22kg silica fume, 679.80kg shale sand, 190kg water, 83.44kg sodium silicate and 58.57kg potassium carbonate respectively;
[0068] 2) Pour the shale sand into the mixer and stir for 1.5 minutes;
[0069] 3) Add slag powder and silica fume into the mixer and continue mixing for 1.5 minutes;
[0070] 4) Premix water, potassium carbonate and sodium silicate to obtain a composite alkali activator, add the composite alkali activator into a mixer and continue stirring for 2 minutes to obtain alkali slag lightweight high-strength concrete.
[0071] Example 2
[0072] This embodiment provides an alkali-slag lightweight high-strength concrete, and the preparation method of the alkali-slag lightweight high-strength concrete comprises the following steps:
[0073] 1. Calculate the mix ratio between the components:
[0074] The water-cement ratio, water consumption, potassium carbonate and sodium silicate dosage set in this embodiment are consistent with those in Example 1, and the total mass of the cementitious material is also consistent with that in Example 1, but the cementitious system is replaced by a mixed system consisting of slag powder, silica ash and hollow glass microspheres, and the mass proportions of the three are 74%, 20% and 6%, respectively, i.e., 611.3 kg of slag powder, 165.22 kg of silica ash and 49.57 kg of hollow glass microspheres.
[0075] The amount of shale sand is calculated according to the following formula:
[0076]
[0077] m s =V s ρ s =0.38×1545=587.1kg;
[0078] Among them, m1 is the mass of slag powder, m2 is the mass of silica fume, m3 is the mass of composite alkali activator, and m s is the amount of shale sand, ρ1 is the density of slag powder, ρ2 is the density of silica fume, ρ3 is the density of composite alkali activator, ρ s is the density of shale sand, V s is the absolute volume of shale sand, S p is the absolute volume sand ratio, m4 is the mass of the hollow glass microspheres, and ρ4 is the density of the hollow glass microspheres.
[0079] 2. Mixing, molding and curing:
[0080] 1) According to the above calculation results, weigh 611.3kg slag powder, 165.22kg silica fume, 49.57kg hollow glass microspheres, 587.1kg shale sand, 190kg water, 83.44kg sodium silicate and 58.57kg potassium carbonate respectively;
[0081] 2) The subsequent operations are the same as in Example 1.
[0082] Example 3
[0083] This embodiment provides an alkali-slag lightweight high-strength concrete, and the preparation method of the alkali-slag lightweight high-strength concrete comprises the following steps:
[0084] 1. Calculate the mix ratio between the components:
[0085] The water-cement ratio, water consumption, potassium carbonate and sodium silicate dosage set in this embodiment are consistent with those in Example 1, and the total mass of the cementitious material is also consistent with that in Example 1, but the cementitious system is replaced by a mixed system consisting of slag powder, silica ash and hollow glass microspheres, and the mass proportions of the three are 68%, 20% and 12%, respectively, i.e., 561.74 kg of slag powder, 165.22 kg of silica ash and 99.13 kg of hollow glass microspheres.
[0086] The amount of shale sand is calculated according to the following formula:
[0087]
[0088] m s =V s ρ s =0.31×1545=478.95kg;
[0089] Among them, m1 is the mass of slag powder, m2 is the mass of silica fume, m3 is the mass of composite alkali activator, and m s is the amount of shale sand, ρ1 is the density of slag powder, ρ2 is the density of silica fume, ρ3 is the density of composite alkali activator, ρ s is the density of shale sand, V s is the absolute volume of shale sand, S p is the absolute volume sand ratio, m4 is the mass of the hollow glass microspheres, and ρ4 is the density of the hollow glass microspheres.
[0090] 2. Mixing, molding and curing:
[0091] 1) According to the above calculation results, weigh 561.74kg slag powder, 165.22kg silica fume, 99.13kg hollow glass microspheres, 478.95kg shale sand, 190kg water, 83.44kg sodium silicate and 58.57kg potassium carbonate respectively;
[0092] 2) The subsequent operations are the same as in Example 1.
[0093] Comparative Example 1
[0094] This comparative example provides an alkali-slag lightweight high-strength concrete, which differs from Example 1 only in that 679.80 kg of shale sand is replaced by a mixture of 231.75 kg of shale sand and 379.03 kg of shale ceramsite, and the remaining raw material components and preparation methods are the same.
[0095] Comparative Example 2
[0096] This comparative example provides an ordinary high-strength concrete, the composition ratio of which is as follows: 414kg of cement, 50kg of slag powder, 8kg of silica fume, 775kg of sand, 1069kg of stone, 190kg of water and 4.8kg of admixture; wherein the cement grade is 52.5, the sand is river sand, and the admixture is a polycarboxylic acid high-performance water-reducing agent.
[0097] Test example
[0098] This test example tests the performance indicators of the concrete provided by Examples 1 to 3 and Comparative Examples 1 to 2, including apparent density, 28d compressive strength and 28d splitting tensile strength; the specific test methods and results are as follows:
[0099] 1. Prepare the concrete sample to be tested:
[0100] The concrete provided in Examples 1 to 3 and Comparative Examples 1 to 2 were respectively placed in molds and rammed into shape; after standing for 12 hours, the concrete was demoulded and transferred to a curing box for curing at 20° C. and a relative humidity of 95% for 28 days to obtain concrete samples to be tested.
[0101] 2. Performance testing:
[0102] This test example refers to JGJVT 12-2019 "Technical Standard for Application of Lightweight Aggregate Concrete" and GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete" to test the apparent density, 28d compressive strength and 28d splitting tensile strength. Examples 1 to 3 and Comparative Example 1 use specific composition ratios as shown in Table 4, and the results are shown in Table 5.
[0103] Table 4 Concrete component ratios provided by Examples 1 to 3 and Comparative Example 1 (kg / m 3 )
[0104]
[0105] Table 5 Mechanical properties of concrete provided by Examples 1 to 3 and Comparative Examples 1 to 2
[0106]
[0107]
[0108] From the results in Table 5, we can see that:
[0109] 1) The alkali-slag lightweight high-strength concrete provided in Examples 1 to 3 uses lightweight aggregate (shale sand) instead of ordinary aggregate (sand, stone) used in Comparative Example 2. Compared with ordinary aggregate, the amount of shale sand in concrete is lower, and the mechanical strength close to or exceeding that of ordinary high-strength concrete can be achieved with low-amount aggregate, which can save resources and conform to the concept of sustainable development; and the apparent density of Examples 1 to 3 is also much lower than that of Comparative Example 2. Compared with the traditional high-strength concrete system, the concrete provided by the present invention has a lighter deadweight and is more suitable for construction projects that require concrete weight while maintaining good mechanical properties;
[0110] 2) Compared with Comparative Example 1, the alkali-slag lightweight high-strength concrete provided in Example 1 uses shale sand as the only aggregate instead of using shale ceramsite as a coarse aggregate, which helps to improve the overall mechanical properties of the concrete. The 28-day compressive strength and 28-day splitting tensile strength of Example 1 are both better than those of Comparative Example 1;
[0111] 3) In the formula provided in Example 1, slag powder has the highest density among all raw materials. Therefore, the present invention adds high-performance hollow glass microspheres in Examples 2 and 3 to replace part of the slag powder to further reduce the density of the concrete. Although it has a certain effect on the mechanical strength, its apparent density is significantly reduced; under the condition that the mechanical strength is still on par with that of ordinary high-strength concrete, the alkali slag lightweight high-strength concrete provided in Examples 2 to 3 is more suitable for construction projects with strict requirements on the weight of concrete, and its overall performance is still better than that of Comparative Example 1.
[0112] In summary, the alkali-slag lightweight high-strength concrete provided by the present invention is obtained by combining an alkali-slag cementitious material and a lightweight high-strength concrete. The alkali-slag cementitious material can select industrial solid wastes such as silica fume and granulated blast furnace slag powder to completely replace cement, thereby reducing carbon emissions; and the shale sand obtained by crushing shale ceramsite is selected as aggregate, which can improve the overall mechanical properties of the concrete; the addition of hollow glass microspheres replaces part of the slag powder, further reducing the density of the concrete, making the concrete more suitable for projects with requirements on the weight of the concrete.
[0113] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. An alkali-slag lightweight high-strength concrete, characterized in that: The alkali slag lightweight high-strength concrete comprises the following components: cementitious material, shale pottery sand and composite alkali activator; The cementitious material includes slag powder and silica fume; The composite alkali activator comprises sodium silicate and potassium carbonate.
2. The alkali-slag lightweight high-strength concrete according to claim 1, characterized in that: The alkali slag lightweight high-strength concrete comprises the following components in parts by weight: 700-900 parts of cementitious material, 400-700 parts of shale pottery sand and 100-200 parts of composite alkali activator; Preferably, the mass ratio of sodium silicate to potassium carbonate in the composite alkali activator is (1-2):1; Preferably, the mass ratio of slag powder to silica fume in the cementitious material is (6-9):
2.
3. The alkali-slag lightweight high-strength concrete according to claim 1, characterized in that: The gelling material also includes hollow glass microspheres.
4. The alkali-slag lightweight high-strength concrete according to claim 1, characterized in that: The particle size of the shale ceramic sand is 0.15-4.75 mm.
5. The alkali-slag lightweight high-strength concrete according to claim 3, characterized in that: The true density of the hollow glass microspheres is 0.4 to 0.8 g / cm 3 ; And / or, the bulk density of the hollow glass microspheres is 0.25 to 0.5 g / cm 3 .
6. The alkali-slag lightweight high-strength concrete according to claim 3, characterized in that: The mass ratio of the hollow glass microspheres to the silica fume is 10:(2-7).
7. The alkali-slag lightweight high-strength concrete according to claim 1, characterized in that: The apparent density of the alkali slag lightweight high-strength concrete is 1400-1700 kg / m 3 .
8. The alkali-slag lightweight high-strength concrete according to claim 1, characterized in that: The apparent density of the shale ceramic sand is 1400-1700 kg / m 3 .
9. The method for preparing the alkali-slag lightweight high-strength concrete according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: stirring shale pottery sand, adding a cementitious material and mixing evenly to obtain a cementitious mixture; The sodium silicate and potassium carbonate are mixed with water to obtain a composite alkali activator, and the composite alkali activator is mixed with a cementitious mixture to obtain an alkali-slag lightweight high-strength concrete.
10. Use of the alkali-slag lightweight high-strength concrete as claimed in any one of claims 1 to 8 in the preparation of lightweight concrete panels.